A convenient way of activating carbon quantum dots and the efficient isolation. (August 2018) - Kuai, Yong; Fang, Raohao; Zhang, Changchang; Liu, Xiang; Ma, Liang
Graphical abstract: Highlights: Chemical tuning with N-hydroxysuccinimide on carbon quantum dots (CQDs) was realized. N-hydroxysuccinimide-modified CQDs were isolated eifficiently from the mixtures. The modified CQDs could be bonded with BSA for the fluorescent labeling. Abstract: Photoluminescence of carbon quantum dots (CQDs) attracts extensive interests. Chemical modifications in a proper way on CQDs are vital for their applications. However, isolating the modified CQDs efficiently from the mixture is still a challenge. Conventional dialysis isolation did not effect at all since the unremarkable changes in size of the modified CQDs. Herein active N-hydroxysuccinimide (NHS) ester was introduced chemically onto the CQDs in very mild conditions, which was demonstrated by IR and X-ray photoelectron spectra. Such activated CQDs could be extracted by ethyl acetate from the mixture efficiently and conveniently which was confirmed by photoluminescence spectra. Experimental results also demonstrated the low cytotoxicity and the high stability against photo-bleaching of the CQDs-NHS. The high reactivity of NHS moiety was demonstrated by the reaction with bovine serum albumin, which revealed in an experiment of sodium dodecyl sulfate polyacrylamide gel electropheresis and the fluorescence imaging.